Hybrid κ-carrageenan-based polymers showing "schizophrenic" lower and upper critical solution temperatures and potassium responsiveness - Loukotová, L; Bogomolova, A; Konefal, R; Špírková, M; Štěpánek, P; Hrubý, M (Carbohydrate polymers, 2019)
Novel multiresponsive hybrid biocompatible systems of κ-carrageenan-graft-poly(2-isopropyl-2-oxazoline-co-2-butyl-2-oxazoline)s with unique combination of responsiveness to external stimuli were synthesized and studied. The polymer thermoresponsive behavior proved the existence of both lower and upper critical solution temperatures in aqueous milieu, forming gel at lower temperature, a solution at room temperature and cloudy nanophase-separated dispersion at elevated temperature. The limit temperatures can easily be adjusted by the polyoxazoline graft length and grafting density. Moreover, the polymer behavior is additionally dependent on the concentration of potassium ions. The polymers behave similarly as the original κ-carrageenan, and thus, the poly(2-alkyl-2-oxazoline) grafts do not decrease the ability of the κ-carrageenan to form the self-assembled structures. Molecular principles beyond this multistimuli-responsive behavior were elucidated with the use of dynamic light scattering, magnetic resonance and fluorescence measurements as well as atomic force microscopy. These polymers could be used in a wide range of biological applications demanding thermo- and potassium-responsiveness.
Keywords: LCST; Polyoxazoline; UCST; Carrageenan; Potassium-responsiveness